2013
DOI: 10.1158/1541-7786.mcr-12-0575
|View full text |Cite
|
Sign up to set email alerts
|

TDP1 and PARP1 Deficiency Are Cytotoxic to Rhabdomyosarcoma Cells

Abstract: Selective targeting of TDP1 and/or PARP-1 in rhabdomyosarcoma induces cytotoxicity and sensitizes to DNA damaging agents.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 51 publications
0
38
0
Order By: Relevance
“…Tdp1 expression is increased in several specific types of cancers including non-small cell lung cancers (58), Dukes C colorectal cancers (57), breast cancer cell lines (89), and some RMSs (56). We show that high levels of CIN in RH30 RMS cells can be partially rescued by the knockdown of TDP1 (Fig.…”
Section: Rms Lines Expressingmentioning
confidence: 68%
See 2 more Smart Citations
“…Tdp1 expression is increased in several specific types of cancers including non-small cell lung cancers (58), Dukes C colorectal cancers (57), breast cancer cell lines (89), and some RMSs (56). We show that high levels of CIN in RH30 RMS cells can be partially rescued by the knockdown of TDP1 (Fig.…”
Section: Rms Lines Expressingmentioning
confidence: 68%
“…To further explore the link between increased hTdp1 expression and CIN, we focused on RMS, one of the most common soft tissue sarcomas in children (59). Some RMS tumors have elevated hTdp1 at both the mRNA and protein levels (56). Using metaphase spreads, we examined whether elevated hTdp1 levels caused CIN in RMS cells by comparing chromosomal abnormalities in RH30 cells, which have high levels of Tdp1 relative to control human skeletal muscle (HSM) cells (56).…”
Section: Rms Lines Expressingmentioning
confidence: 99%
See 1 more Smart Citation
“…Talazoparib as a single agent was not active against Ewing sarcoma xenografts (56). Rhabdomyosarcoma also tend to high in PARP1 (Figure 6) (57). Expression of polo-like kinase 2 (PLK2) and miRs -100, -574, -22, -21 and -30 were negatively correlated with talazoparib sensitivity (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was reported that the decrease in RAD51 levels led to increased levels of g-H2AX expression and cleavage of PARP. In a research endeavor relating to soft tissue sarcoma and rhabdomyosarcoma (RMS), Fam and coworkers have demonstrated that increased levels of expression of TDP1 and PARP1 were observed in RMS [48]. Various experiments were conducted to identify the resistance to a camptothecin analog, irinotecan, which was due to overexpression of TDP1 and further knockdown of TDP1 sensitized the RMS to irinotecan.…”
Section: Parp Inhibitors In Dna Damage Responsementioning
confidence: 99%